Argumentos x núcleos focales: el estatus de clíticos que duplican SSNN en español - Correa, Paulo (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
This paper presents a generative analysis of accusative clitics involved in clitic-doubling constructions in Spanish. It will be shown that this kind of clitic does not constitute a single unitary element, but must be classified in two types, the anaphoric one and the deictic one. Whereas the former have been analyzed in early works such as Jaeggli (1982, 1986b), the occurrence of the latter may be related to the focalization of a constituent in situ. This analysis parallels with Suñer (1995), treating negative concord as a polarity phenomena, once the present work reveals a correlation between the syntactic realization of negative words in negative polarity and the realization of a clitic doubling a focused NP.